Beyond the classics: A comprehensive look at concept analysis methods in nursing education and research - Joko Gunawan; Yupin Aungsuroch; Colleen Marzilli (Belitung Raya Foundation, Indonesia, 2023)
This editorial presents eight concept analysis methods for use in nursing research and education. In addition to the two classical methods of Walker and Avant’s and Rodgers’ concept analysis approaches that are typically utilized in nursing education and briefly discussed within this editorial, six additional methods are also presented including Schwartz-Barcott and Kim’s Hybrid model, Chinn and Kramer’s approach, Simultaneous Concept Analysis, Pragmatic Utility, Principle-Based Concept Analysis, and Semantic Concept Analysis. By familiarizing nursing educators, researchers, and students with these methods, educators can enhance their critical thinking and understanding of complex nursing concepts, preparing them for enhanced, multi-faceted contributions to nursing science.